Plant gene containment. - Oliver, Melvin J. (John Wiley & Sons, 2012)
Gene Containment provides a comprehensive look at genetically modified organisms and the strategies and implementation of key methods to gene containment. The book is divided into 5 parts: An Introduction that discusses the need for biotechnology and GMOs, Section 1 looks at the need for gene containment, Part II discusses varying strategies for gene containment, section III explores the assessment of gene containment approaches, and section IV covers the steps involved in implementing gene containment. Gene Containment will provide a thorough and up to date look at gene containment research a.